From Hero to Outcast: Marginalization and Social Exclusion in Bhasa’s Karnabharam - Shantanu Shivajirao Patil (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Mahakavi Bhasa’s play Karnabharam offers a profound exploration of the theme of marginalization through the tragic figure of Karna, whose journey from celebrated warrior to social outcast serves as a powerful commentary on caste-based exclusion. The play explores the psychological torment and inner conflict experienced by Karna as he struggles with the revelation of his true identity and the social denial. Rather than being solely a personal tragedy, Karna’s downfall reflects the broader systemic injustice faced by individuals marginalized due to their birth, irrespective of their virtues or accomplishments. Bhasa presents Karna not only as a heroic figure torn between loyalty and self-worth, but also as a symbol of the countless individuals who are denied dignity and recognition because of rigid social hierarchies. The emotional depth of Karna’s character is marked by anguish, dignity, and resilience that magnify the evaluation of a society that privileges heredity over merit. Through Karnabharam, Bhasa foregrounds the human cost of exclusion, appealing to audiences to reflect on the enduring consequences of discrimination. The play ultimately serves as a timeless narrative that resonates with contemporary struggles for equality and social justice, making Karna’s plight a universal metaphor for the marginalized. By portraying the intersection of personal valour and societal prejudice, Karnabharam not only humanizes the outcast but also challenges the notions of hierarchy and forces audiences to reconsider the values by which individuals are judged.